Hubungan Tingkat Pengetahuan dengan Perilaku Pencegahan COVID-19 di Desa Lebak Peniangan Lampung - Dwi Wulandari; Nia Triswanti; Vera Yulyani (ARTERI : Jurnal Ilmu Kesehatan, 2021)
Relationship COVID-19 knowledge level with COVID-19 prevention behavior in Lebak Peniangan Village, Rebang Tangkas Way Kanan District, Lampung, 2021. Corona Virus (CoV) is an ongoing global talk of all circles in the world from December 2019 to April 2021, which is still a problematic topic. The novel coronavirus (2019-nCoV) is a new type of coronavirus that has never been previously identified in humans. It can cause illnesses ranging from the common cold to serious illnesses such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). COVID-19 can spread from person to person especially when an infected person is in close contact with another person. The knowledge gained can encourage people to take actions such as complying with health protocols recommended by the government and taking basic protection, namely implementing 3M and 3T during the COVID-19 pandemic. This study aimed to analyze the relationship between COVID-19 knowledge level and COVID-19 prevention behavior in Lebak Peniangan Village, Rebang Tangkas Way Kanan District, Lampung. This research was a quantitative study with a crosssectional design. The population was determined based on family cards of 1500 households. The sample was obtained using a random sampling technique of 306 respondents. The researcher collected knowledge and behavior data using a questionnaire and analyzed using the Chi Square test. The result of Chi Square test on the respondent's knowledge and behavior showed p value = 0.000 (p<0.05) which means that there is a significant relationship between the level of knowledge and COVID-19 prevention behavior in Lebak Peniangan Village, Rebang Tangkas Way Kanan District, Lampung, 2021.The results showed that most of the respondents' knowledge about COVID-19 was in a good category with 258 respondents (84.3%). The behavior of respondents in efforts to prevent COVID-19 was mostly in the moderate category with 218 respondents (71.2%). From the research results, it can be concluded that there is a relationship between respondents' COVID-19 knowledge and COVID-19 prevention behavior in the community. The public needs to know more about COVID-19 to improve prevention behavior.